Growth of pitaya seedlings according to the type of substrate and the frequency of irrigation - da Cunha Guimarães, Rodrigo Rafael; de Oliveira Barradas, Jonathas; Lima da Silva, Raimundo Thiago; Oliveira Moreira, Wendel Kaian; Almeida de Souza, Samara Ketely (Revista Ceres, 2025)
The objective of this study was to evaluate the development of pitaya cuttings in different substrates under different frequencies of irrigation. The experiment was conducted from January to May 2017 in a greenhouse at the Universidade Federal Rural da Amazônia, Capitão Poço, Pará, Brazil. A completely randomized 3 × 7 factorial design with four replicates was used. Pitaya plants were grown from cuttings in three types of substrates (S1: potting soil; S2: potting soil + cattle manure + wood shavings; and S3: washed sand) under seven irrigation frequencies (24, 48, 72, 96, 120, 144, and 168 h). There was interaction between treatments for root dry matter production, root length variables, the other variables showed no interaction between treatments. The greater development of new and vigorous tissues of the aerial part, the substrates with composition black earth and black earth + manure + sawdust are indicated, and the adoption of the irrigation frequency of 72 h or 96 h. The use of substrate based on black earth + manure + sawdust, allows savings in the rational use of water and energy with the application of the 96 h irrigation frequencies, maintaining satisfactory levels of development to the plant. The washed sand substrate can be used for propagation when this material is abundant, however, greater attention should be paid to the supply of water and nutrients to the plant.